A CASE OF ESPIONAGE FROM THE 18TH CENTURY: A RECONNAISSANCE TRIP TO POLA MADE BY A GROUP OF INTELLIGENCE OFFICERS OF THE HABSBURG EMPEROR. NOTES FROM THE ANONYMOUS REPORT TO THE GOVERNOR OF POLA DATED 12 APRIL 1788 - Sandro Cergna (Studia Polensia, 2019)
ror Joseph II from 1788, from Rijeka to Pula, while passing through several towns and villages of the eastern coast of Istria. The original document, that is, an anonymous report addressed to the Governor of the Istrian city, has been preserved in the archives of the University Library in Pula. It describes the journey of the Austro-Hungarian group and, in more detail, their encounter with an anonymous intelligence officer of the then prefect of the Istrian city, Angelo Maria Orio, who was also not named in the report. This document, significant as a travelogue as well as in terms of culture, also contains interesting historical and political information, such as the hidden reasons why these famous characters sought as much information as possible about Pula, its port and transport routes; their interest in economic policy and defence of the Venetian Republic in this area not even ten years before its fall. It also describes the political situation in Istria and the state border situation at the time.